2020
DOI: 10.1029/2019jb018797
|View full text |Cite
|
Sign up to set email alerts
|

Time‐Dependent Hydraulic Fracture Initiation

Abstract: Rocks are known to fail in a time‐dependent manner similar to many brittle and quasi‐brittle materials. However, observed time dependence of hydraulic fracture initiation has ubiquitously been attributed to fluid flow‐related mechanisms without consideration of the intrinsic time dependence of rock failure. Laboratory delayed hydraulic fracturing breakdown experiments on three rocks (granite, sandstone, and limestone) show sensitivity to rock properties associated with subcritical crack growth as well as fluid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The disagreement between theoretical predictions and laboratory observations in the BP can be induced by (1) the compressibility of the injection system, (2) the flow of a viscous fluid into the fracture, and (3) the far-field stress deviator. In addition, a recent study pointed out the time dependence of hydraulic fracture initiation in granite as well as other types of rock, such as limestone and sandstone, in which hydraulic fracture initiation is delayed when the borehole is pressurized under instantaneous initiation pressure, and the time delay is increased for fracturing with a higher-viscosity fluid (Lu et al, 2015(Lu et al, , 2020. The instantaneous fluid pressure in the borehole is controlled by the injection or pressurization rate as well by the compressibility of the injection system.…”
Section: Infiltration Zone and Breakdown Modelsmentioning
confidence: 99%
“…The disagreement between theoretical predictions and laboratory observations in the BP can be induced by (1) the compressibility of the injection system, (2) the flow of a viscous fluid into the fracture, and (3) the far-field stress deviator. In addition, a recent study pointed out the time dependence of hydraulic fracture initiation in granite as well as other types of rock, such as limestone and sandstone, in which hydraulic fracture initiation is delayed when the borehole is pressurized under instantaneous initiation pressure, and the time delay is increased for fracturing with a higher-viscosity fluid (Lu et al, 2015(Lu et al, , 2020. The instantaneous fluid pressure in the borehole is controlled by the injection or pressurization rate as well by the compressibility of the injection system.…”
Section: Infiltration Zone and Breakdown Modelsmentioning
confidence: 99%
“…33 A few studies have discussed delayed hydraulic fracture initiation, in which the time of breakdown (in logarithmic scale) decreases with increasing wellbore pressure. 16,48,49 The subcritical crack growth index was employed to predict the fracture-tip velocity or the fracture growth rate assuming that the fracture can be initiated when the Mode-I stress intensity is lower than the critical fracture toughness. 16 A recent study employed semi-circular bend tests on sandstone composed of 5% cement of argillaceous materials and investigated the effects of waterand acid erosions and found that fluid erosions in sandstone significantly influence the subcritical crack-growth process due to chemical reactions that were pertinent to the cementing agent and the grain boundaries of the sandstone.…”
Section: High-cycle Fatiguementioning
confidence: 99%
“…11,12 While crack nucleation models are available for the mechanical loading of crystalline (wing cracks) 13 and sedimentary rock (pore cracks), 14 fluid-driven fracture nucleus and growth path models remain sparse. For example, Lu et al (2018Lu et al ( , 2019) presented a time-dependent hydraulic fracture initiation model that incorporates a subcritical crack growth index and applied this model to data from laboratory experiments on granite, sandstone, and limestone. 15,16 Both the stress intensity factor at the fracture tip and the fracture toughness (critical stress intensity factor of Mode I cracks) play a key role in the damage mechanics of rock fatigue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These early solutions were limited in terms of relevant theories and computational approaches. More rigorous theories (e.g., linear elastic fracture mechanics [LEFMs] and Green's function‐based elastic relationships) and approaches (e.g., the displacement discontinuity method [DDM]) applied to the theoretical study of hydraulic fracturing in the past two decades (Adachi & Detournay, 2002, 2008; Bunger et al., 2005; Chen, Barron, et al., 2018; Lu et al., 2020) have not been employed to theoretically study subsurface thermal fracturing.…”
Section: Introductionmentioning
confidence: 99%